De invloed van de coronacrisis op de relatieve verdeling van zorg door moeders en vaders. Een longitudinaal perspectief - André, Stéfanie; Yerkes, Mara A.; Remery, Chantal (Mens & Maatschappij, 2021)
Angaben zum Inhalt: „The influence of the COVID-19 pandemic on the relative division of care tasks between mothers and fathers: a longitudinal perspective. For many parents, the combination of work and care was already demanding and unevenly distributed prior to the COVID-19 pandemic. The pandemic has clearly influenced the relative division of care tasks, but how and why remains unclear. We use longitudinal panel data from the LISS panel, collected in April, June and November 2020, to analyze the influence of the COVID-19 pandemic on the relative distribution of care by mothers and fathers in the Netherlands. A complex picture emerges from these longitudinal analyses, and several theoretical perspectives appear to be relevant. We conclude that time availability mainly has an effect at the beginning of the pandemic, while relative resources play a role the longer the pandemic endures.“
Keywords: Geschlechterverhältnis; Hausarbeit

Opvattingen over gender en het opvoeden van kleine kinderen voor en na de eerste lockdown in Nederland - Begall, Katia; Verbakel, Ellen (Mens & Maatschappij, 2021)
Angaben zum Inhalt: „Attitudes about gender and the care for small children before and after the first lockdown in the Netherlands The COVID-19 pandemic has led to major changes in the division of paid and unpaid work in many Dutch households. Before the pandemic, work-care patterns were relatively traditional in the majority of families in the Netherlands, with women performing more unpaid tasks and men more paid work. These patterns were disrupted during the lockdown by the obligation to work from home and formal and informal childcare being unavailable. This meant that fathers were much more exposed to care and household tasks than before the pandemic. This effect was potentially reinforced by the fact that many ‘essential workers’ in education and healthcare were female, leaving their male partner to take over (extra) care tasks at home. But did these changes in the division of tasks also affect normative attitudes about gender and care? In this study we aim to answer this question using longitudinal data collected among 300 respondents in the Netherlands before (early 2019/2020) and after (July 2020) the first lockdown. We expect that attitudes about men’s caring capabilities have become more positive in partnered men and women if the male partner was working from home. The empirical results show that attitudes about gender roles regarding child rearing have become more traditional after the lockdown and this is particularly the case for men who worked from home while their partner continued to work outside the home.“
Keywords: Geschlechterverhältnis; Hausarbeit

De coronacrisis is een feministisch drama. Hoe gaan we dit samen oplossen? - La Grouw, Yvonne (Beleid en Maatschappij, 2021)
Keywords: Geschlechterverhältnis; Open Access/Volltext

Gender en migratie in tijden van pandemie - Miri, Amal; Praag, Lore Van (De stad beter na corona? Reflecties over een gezondere en meer rechtvaardige stad, 2021)
Keywords: Antwerpen; Geschlechterverhältnis; Migration; Soziale Integration; Soziale Situation

COGIS-NL. COVID Gender (In)equality Survey Netherlands. Second policy brief, results from June - Yerkes, Mara; André, Stéfanie; Besamusca, Janna; Hummel, Bryn; Remery, Chantal; Zwan, Roos van der; Kruyen, Peter; Beckers, Debby; Geurts, Sabine (Universiteit Utrecht, Universiteit van Amsterdam, Radboud Universiteit, 2020)
Keywords: Eltern; Geschlechterverhältnis; Gleichberechtigung; Open Access/Volltext; Panelanalyse; Statistik; Umfrage